The Comparative Effectiveness of Botulinum Toxin-A Injection Therapy Versus Augmentation Uretero-Enterocystoplasty for the Treatment of Lower Urinary Tract Dysfunction - Xuesheng Wang; Zhonghan Zhou; Limin Liao (International Neurourology Journal, 2023)
Purpose We investigated the effectiveness of intravesical botulinum toxin-A (BTX-A) injection therapy in patients with lower urinary tract dysfunction (LUTD) and upper urinary tract (UUT) deterioration and evaluated whether BTX-A injection therapy could substitute for augmentation uretero-enterocystoplasty (AUEC). Methods Data from a prospective, single-center cohort from 2017–2021 were analyzed. Patients were divided into 2 treatment groups: AUEC and BTX-A (i.e., patients who declined AUEC). Bladder and UUT functions were assessed by comparing clinical information, urodynamic data, laboratory results, and imaging records. Results In total, 121 patients were enrolled (BTX-A group: 41 patients; AUEC group: 80 patients). The BTX-A group showed a reduced maximum detrusor pressure and increases in the maximum bladder volume and bladder compliance (P<0.05). However, in follow-up evaluations, significantly smaller improvements (all P<0.05) in urodynamic parameters were found in the BTX-A group than in the AUEC group. Notably, there was no significant improvement in vesicoureteral reflux (VUR; P=0.66) or upper urinary tract dilatation (UUTD; P=0.75) in the BTX-A group, and no statistically significant difference in serum creatinine (Scr) levels or the estimated glomerular filtration rate (eGFR) was observed in the follow-up evaluations (all P>0.05). Both VUR and UUTD improved significantly in the AUEC group, and the Scr and eGFR levels significantly improved after AUEC relative to baseline levels (P<0.05). The reduction in the Scr level was significantly lower in the BTX-A group than in the AUEC group during 0–15 months of follow-up (Scr reduction differences, −1.36; P<0.01). Conclusions Although BTX-A injection therapy was effective for improving bladder function, BTX-A injections did not alleviate UUT deterioration in this study, particularly in patients with advanced-stage LUTD. Conversely, AUEC for LUTD has a well-established role in improving UUT function. Hence, BTX-A injection therapy should not replace AUEC to ameliorate UUT impairment and protect UUT function.